Breach of trust [compact disc, unabridged] - Ellis, David, 1967- (Brilliance Audio, 2010)
Jason Kolarich has spent the last year struggling to recover from the horrific deaths of his wife and baby daughter. Kolarich blames himself not only for the deaths of his wife and child, but for the informant's murder as well. Unfortunately, Kolarich's guns-blazing approach to justice lands him smack in the middle of an FBI probe of the deeply corrupt and notoriously foul-mouthed governor of Illinois. To avoid jail, Kolarich must enter a world of wiretaps, double-dealing, and kickbacks.